Where do balloons go? : an uplifting mystery - Curtis, Jamie Lee, 1958-; Cornell, Laura (New York : Joanna Cotler Books, 2000)
A child wonders about what happens to a balloon that is let go, as a parent would wonder about what might happen to a child once he leaves home.
1.8
K-3
K-3
School Library Journal
Publisher's Weekly
New York Times
Keywords: Balloons -- Fiction; Stories in rhyme; Balloons -- Fiction; Stories in rhyme